The end of cheap China : economic and cultural trends that will disrupt the world - Rein, Shaun, 1977- (Hoboken : Wiley, 2014)
"An expose; on how the rise of China will affect the American way of lifeThe End of Cheap China is a fun, riveting, must-read book not only for people doing business in China but for anyone interested in understanding the forces that are changing the world.Many Americans know China for manufacturing cheap products, thanks largely to the country's vast supply of low-cost workers. But China is changing, and the glut of cheap labor that has made everyday low prices possible is drying up as the Chinese people seek not to make iPhones, but to buy them. Shaun Rein, Founder of the China Market Research Group, puts China's continuing transformation from producer to large-scale consumer - a process that is farther along than most economists think - under the microscope, examining eight megatrends that are catalyzing change in China and posing threats to Americans' consumption-driven way of life.Rein takes an engaging and informative approach to examining the extraordinary changes taking place across all levels of Chinese society, talking to everyone from Chinese billionaires and senior government officials to poor migrant workers and even prostitutes. He draws on personal stories and experiences from living in China since the 1990s as well as hard economic data. Each chapter focuses on a different aspect of China's transformation, from fast-improving Chinese companies to confident, optimistic Chinese women to the role of China's government, and at the end breaks down key lessons for readers to take away.The End of Cheap China shows: How rising labor and real estate costs are forcing manufacturers of cheap Chinese products to close, relocate, or move up the value stream How a restructuring economy moving away from exports to domestic consumption, and rising incomes will create opportunities for foreign brands to sell products in China rather than just producing there How Chinese consumption will build pressure on the global commodities markets, causing both inflation and friction with other nations How China's economic transformation spells the end of cheap consumption for Americans China's days as a low cost production center are numbered. The End of Cheap China exposes the end of America's consumerist way of life and gives clear advice on how companies can succeed in the new world order"--
Includes index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Labor -- China; Costs, Industrial -- China; Consumption (Economics) -- China; China -- Economic conditions -- 2000-; China -- Social conditions -- 2000-; China -- Commerce; Electronic books